Pengaruh Bauran Pemasaran Terhadap Loyalitas Pelanggan pada Konsumen Alfamart di Kecamatan Mande (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of marketing mix consisting of product, price, place and promotion on customer loyalty of Alfamart consumers in Mande sub-district. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to 46 Alfamart consumer respondents. The results of the analysis show that simultaneously the marketing mix has a significant effect on customer loyalty. Partially, product and promotion variables have the most dominant influence. These findings indicate that the right marketing strategy can increase customer loyalty. Therefore, Alfamart is advised to continue to improve product quality and promotion effectiveness in order to maintain and attract loyal customers.